The effect of light attractor color in pelagic longline fisheries - Afonso, André S. (2021)
Improving the selectivity of the fishing gear is one of the most promising methods to mitigate deleterious impacts of longline fisheries upon bycatch species. Light lures have recently become widespread in epipelagic longline fisheries since they increase the catch rates of valuable target species such as swordfish and tunas. Yet, little is known about their effect upon the incidence of bycatch. Here, we compared the catchability of target and bycatch species in a pelagic longline fishery targeting swordfish and tunas equipped with light attractors with three different colors to ascertain if any of the light attractor colors would enhance the selectivity of the fishing gear. A total of 3488 individuals were caught across 57 fishing sets. The proportion of target species to bycatch species was high (58–65 %) in each color treatment. Overall, green attractors (peak wavelength at 525 nm) exhibited the highest catch rates of target species, but they were also responsible for the highest incidence of bycatch, rendering 73 % and 82 % of the blue shark and sea turtle catch, respectively. Blue (peak wavelength at 465 nm) and white attractors caught significantly less individuals of both target and bycatch species. Further, significant interactions between light attractor color and the intensity of lunar illumination were observed for most species analyzed. Differences in the catchability of bycatch such as blue sharks and white marlins across attractor color treatments were more conspicuous at high lunar illumination levels (i.e. full moon periods), when white attractors rendered the lowest catch of these taxa. In contrast, the catchability of target species such as swordfish, yellowfin tuna and albacore showed greater differences between treatments at low illumination levels (i.e. new moon periods). The observed differences in the performance of the three light attractor colors across the lunar cycle might provide an opportunity to mitigate bycatch incidence in longline fisheries. Yet, further research is required to fully understand the combined effects of light lures and lunar illumination on the behavioral responses of pelagic species.